Smart IoT Relay Monitoring Box for Real-Time Monitoring and Control of Electrical Energy Consumption - Muslihi, Muhammad Takdir; Syafie, Lukman; Alghamdi, Mona Ahmad; Puteri, Annisa Nurul; Achmad, Andita Dani (Jurusan Pendidikan Teknik Elektro, 2026)
Background: The rapid increase in electricity consumption, particularly the 23.36% rise in Indonesia from 2019 to 2023, highlights the need for more efficient energy management systems. Limited user awareness and the lack of integrated monitoring and control solutions often lead to energy waste. Objective: This study aimed to design and evaluate an Internet of Things (IoT)-based smart relay system for real-time monitoring and remote control of electrical energy consumption. Methods: This study employed an experimental-based system development approach to create a portable prototype. The system integrated an ESP8266 microcontroller, a PZEM-004T sensor, a relay module, and a 16×2 LCD, with data transmitted to a web-based platform for monitoring and control. The system was tested using five different electrical loads, and performance was evaluated by comparing sensor measurements with standard measurement instruments. Results: The system achieved high accuracy in voltage measurement with an average error of 0.58% and moderate accuracy in power measurement with 2.78%. However, current measurement showed a higher average error of 15.06%, indicating sensitivity to fluctuating load conditions. The system supports real-time monitoring and remote control with an average response time of approximately one second. Compared to previous studies, the system demonstrates comparable voltage performance but higher deviation in current measurement. Novelty: This study presents an integrated IoT-based system that combines real-time monitoring, remote control, and energy estimation within a compact and portable platform. The proposed system provides a practical solution to enhance user awareness and enable more efficient energy management, extending beyond conventional monitoring-only systems.